Violence after war and in social transition : What are the needs of children? - Ajduković, Dean (2005)
Among the most prominent consequences of war-related violence in multi-ethnic communities, apart form massive traumatisation and losses, is the community division along ethnic lines. The children growing up in such communities have no choice but to model own inter-group behaviors after the important adults. However, unlike the adults they have no experience of living in the ethnically undivided community and the sense of communality. In fact, children growing up in such social environment have no other experience except conflict with or separation from the other group. In a community that was horrendously destroyed in the recent war, the city of Vukovar, high level of community divide is evident in separated schooling programs, sports, arts, culture, even in coffee shops. Over several years of studying this community using both quantitative and qualitative methods, the effects of the past suffering and ongoing division on the children were identified. Some of these include the following: Members of both ethnic groups disapprove of contacts with the other group, children keep their relations to the own ethnic group, as the adults do, among children there is a tendency to discriminate their peers from the other ethnic group, the children are less supportive of integrated schooling. In fact, the children do not really have a choice of different behaviors because of the social pressures to hold on to the own group. In a community destabilized by the war and with ethnic divisions, social reconstruction model and intervention strategies may increase the capacity of children and their parents to make informed choices about their future. Children should not be expected to reconcile the community, this could not be their task nor responsibility.